Clear Cell Adenocarcinoma of Uterine Cervix: A Single Institution Retrospective Experience - Liu, Zhimin; Li, Junyun; Gu, Haifeng; Tu, Hua; Liu, Guochen; Liu, Jihong (Frontiers in Oncology, 2020)
Purpose: To summarize the clinical characteristics and identify the prognosis of clear cell adenocarcinoma of the uterine cervix (CCAUC) patients without a history of diethylstilbestrol (DES) exposure. Methods: Forty-two patients with CCAUC treated initially at Sun Yat-sen university cancer center between 1985 and 2017 were studied. Results: Of all the CCAUC patients, median age was 47 years old, and the median tumor size was 3 cm. 34 early stage patients (IB=28, IIA=6) underwent radical surgery. 8 advanced stage patients (IIB=8) received concurrent chemoradiotherapy (n=4) or radical surgery (n=4). Survival analysis showed that patients with early stage had a significantly better 5-year PFS and OS than those with advanced stage (p<0.05). The patients with negative pelvic lymph node (PLN) had a significantly better 5-year PFS and OS than those with positive PLN (p<0.05). Radiotherapy (RT) did not affect PFS or OS in early stage patients with intermediate risk factors (p>0.05). Adjuvant chemotherapy (CT) did not affect PFS or OS in early stage patients without risk factors (p>0.05). Conclusion: The FIGO stage and pelvic node status were important prognostic factors for both PFS and OS. For treatment modality, we recommended that radical surgery alone was used in early stage patients without high risk factors. Ovarian preservation in early stage patients involved some risk.